The developmental impact of non-contributory social grants in South Africa : a study of Ezibeleni, Queenstown - Xaba, Mzingaye Brilliant (Rhodes University, Faculty of Humanities, Department of Sociology, 2015)
Amartya Sen argued that poverty was the "deprivation" of the capability to lead a "good life" , therefore ending poverty meant meeting basic physical and social needs, and enabling meaningful economic and political choices. The principal objective of this research was to investigate whether (and if so, in what ways) post-apartheid state-provided non-contributory cash social grants in South Africa reduced "poverty" in Sen's sense. This thesis used Ezibeleni, a historically black working class township at Queenstown, in the Eastern Cape, as a reference area. Using in-depth interviews, it found that social grants did help reduce poverty, both in terms of helping meet basic needs and enabling grant recipients to make more choices, including facilitating job searches and small businesses. However, it was also found that grants fall short of ending poverty, as the grants were too small to adequately cover basic needs in the context of large family sizes, a serious and long-term lack of resources, persistent unemployment, and high indebtedness, and could also enable only a limited expansion of choices. The grants played a positive role, but were inadequate to remove the "unfreedoms" facing the poor.
Keywords: Economic assistance, Domestic -- South Africa; Poor -- South Africa -- Queenstown; Poverty -- South Africa -- Queenstown; South Africa -- Economic conditions -- 1991-; South Africa -- Social conditions -- 1994-